(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Patient care has been transformed by the digitization of healthcare, but there are also serious privacy and data security issues. Protecting sensitive patient data is crucial as telemedicine, electronic health records (EHRs), and Internet of Things-based health monitoring become more commonplace. This study looks at the main risks to patient data in digital settings, assesses the effectiveness of current defenses (such as encryption, access controls, and regulatory compliance), and investigates cutting-edge solutions like blockchain and artificial intelligence (AI)-driven security. We also present case studies of data breaches and their impacts, along with best practices for healthcare organizations. Our findings highlight the need for a multi-layered security approach, continuous staff training, and adaptive policies to mitigate risks in an evolving cyber-threat landscape.